Secretome hypoxia-mesenchymal stem cells decrease tumor necrosis factor-α and interleukin-18 in kidney of type 2 diabetes mellitus model rats - Irawan, Risky Chandra Satria; Putra, Agung; Setyo, Trisnadi; Ghaisani, Shabrina Syifa; Hidayah, Nurul (Universa Medicina, 2023)
Background Type 2 diabetes mellitus (T2DM) is a chronic disease that affects millions of people worldwide and associated with an increased risk of kidney damage caused by prolonged inflammation. Secretome hypoxia- mesenchymal stem cells (SH-MSCs) have been investigated as a potential therapy for kidney inflammation in T2DM, due to their immunomodulatory properties and ability to promote tissue repair. In this study, we investigated the effects of SH-MSCs on tumor necrosis α (TNF-á) and interleukin-18 (IL-18) in the kidney of the T2DM model rats. MethodsA post-test-only control group involving 24 male Wistar rats. The rats were treated with a high-fat diet (HFD) for 4 weeks and streptozotocin-nicotinamide with sucrose solution for 5 days to induce T2DM animal models. Rats were randomly divided into four groups: healthy, control, and groups treated with SH-MSCs T1 and T2, with doses of 250 µL and 500 µL, respectively. TNF-α and IL-18 gene expression was measured by real time polymerase chain reaction (RT-PCR). One Way ANOVA and post-hoc LSD tests were used to determine the significant difference against all groups based on their quantitative measurement. ResultsAdministration of the SH-MSCs at a dose of 500µL (T2) was able to significantly reduce TNF-α and IL-18 gene expression when compared to control (T2DM rat without treatment) (p<0.05), but not significantly when compared to healthy and SH-MSC at a dose of 250µL (T1) group (p>0.05). ConclusionThis study demonstrated that the SH-MSCs decreased the levels of proinflammatory cytokines TNF-α and IL-18 gene expression in the kidney of T2DM model rats.